Fine and coarse dust separation with polarization lidar - Mamouri, Rodanthi-Elisavet; Ansmann, Albert (Atmospheric Measurement Techniques, 2014)
The polarization-lidar photometer networking (POLIPHON) method for separating dust and non-dust aerosol backscatter and extinction, volume, and mass concentration is extended to allow for a height-resolved separation of fine-mode and coarse-mode dust properties in addition. The method is applied to a period with complex aerosol layering of fine-mode background dust from Turkey and Arabian desert dust from Syria. The observation was performed at the combined European Aerosol Research Lidar Network (EARLINET) and Aerosol Robotic Network (AERONET) site of Limassol (34.7° N, 33° E), Cyprus, in September 2011. The dust profiling methodology and case studies are presented. Consistency between the column-integrated optical properties obtained with sun'sky photometer and the respective results derived by means of the new lidar-based method corroborate the applicability of the extended POLIPHON version.